INFLUENCE OF MONITORING AND EVALUATION HUMAN RESOURCES CAPACITY ON PERFOMANCE OF HORTICULTURE PROJECTS IN NAKURU COUNTY, KENYA - CHEBET MUREI, Ms. LILY; KIDOMBO, Prof. HARRIET; GAKUU, Prof. CHRISTOPHER (IJRDO - Journal of Social Science and Humanities Research, 2017)
Human capital development contributes to increased productivity and project performance. Although this may be true, there is little empirical evidence as to what extent monitoring and evaluation human resource capacity in influences performance of horticulture projects. This study sought to establish the extent to which monitoring and evaluation human resource capacity influences performance of horticulture projects in Nakuru County. Study design was cross sectional and a correlation descriptive survey. A mixed method approach was applied. Structured questionnaires of Likert scale, Key Informant Interviews and Focus Group Discussions were the main tools for data collection. Arithmetic mean and standard deviation were generated from the descriptive data. Pearson’s Product Moment Correlation Coefficient(r) was computed. Results showed that M &E human resource capacity had a significant influence on performance of horticulture projects. Recruiting competent M & E staff and building M & E capacity at all levels was recommended.